2018
DOI: 10.1002/chem.201803638
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Manipulation of Supramolecular Chirality using Host–Guest Dynamics between β‐Cyclodextrin and Alkyl Amines

Abstract: Host-guest interactions are widely employed in constructing responsive materials, although less is known to manipulate the chiral property of materials using such host-guest dynamics. With the supramolecular self-assembly based on β-cyclodextrin (β-CD) and alkyl amines (CH(CH)NH), we report that faster host-guest dynamics induces a dipole located above the cavity of β-CD, whereas slower dynamics create in-cavity dipole. These two scenarios correspond to negative and positive chiral signals, respectively. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Huang, Yan ad co-workers reported a chiral supra-amphiphile based on b-cyclodextrin and a long alkyl amine. 106 Under vortex mixing, achiral organic amines CH 3 (CH 2 ) nÀ1 NH 2 (n = 6-10) were added into the saturated solution of b-cyclodextrin. For shorter chain amines of CH 3 (CH 2 ) nÀ1 NH 2 (n = 6, 7), NMR and FT-MS spectra indicated that a host-guest complex was not formed, which was also co-evidenced by no Tyndall effect.…”
Section: Self-assembly Of Cyclodextrin Based Chiral Supra-amphiphilesmentioning
confidence: 99%
“…Huang, Yan ad co-workers reported a chiral supra-amphiphile based on b-cyclodextrin and a long alkyl amine. 106 Under vortex mixing, achiral organic amines CH 3 (CH 2 ) nÀ1 NH 2 (n = 6-10) were added into the saturated solution of b-cyclodextrin. For shorter chain amines of CH 3 (CH 2 ) nÀ1 NH 2 (n = 6, 7), NMR and FT-MS spectra indicated that a host-guest complex was not formed, which was also co-evidenced by no Tyndall effect.…”
Section: Self-assembly Of Cyclodextrin Based Chiral Supra-amphiphilesmentioning
confidence: 99%
“…To further confirm the above postulation, we decided to measure the host–guest dynamics-dependent ICD of the cone-shell self-assemblies since the host–guest dynamics has a great impact on the threading position of the guest in the cavity of α-CyD, which may reverse the ICD at properly designed host dynamics . Both concentrations and host-to-guest ratios are effective protocols to achieve dynamic control . In principle, at lower concentrations, the exchanging rate between the C4AZO molecules in and out of the α-CyD is slower, so that the C4AZO molecules have time to thread deeper in α-CyD.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, if the chromophore is outside of the cavity of CyDs, a negative ICD should be expected . In the past half century, the above Harata–Kodaka rule was extensively utilized to predict the absolute configuration of the achiral guest in the cavity of CyDs but has never been considered in symmetry breaking in racemic self-assembled structures and controls the handedness of supramolecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral recognition also plays a key part in the field of chemical, biological, and pharmaceutical sciences because of the precise orientation of functional groups in chiral molecules [6][7][8][9]. Many active pharmaceutical ingredients (APIs) are chiral and the two enantiomers often present different pharmacokinetic, therapeutic, and toxicological profiles.…”
Section: Introductionmentioning
confidence: 99%